Analisis Pengelolaan Sarana dan Prasarana Pembelajaran - Ria Ramdhiani (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Educational facilities really determine the success of education, because in education facilities and infrastructure play an important role in the learning process. Facilities and infrastructure affect the learning process, thus determining effective and efficient learning. With this research, the researcher will examine the management of facilities and infrastructure inincluding, planning of facilities and infrastructure, procurement of facilities and infrastructure, use of facilities and infrastructure, and maintenance of facilities and infrastructure. This study aims to obtain an overview of the management of facilities and infrastructure in . The approach and method used in this study uses a qualitative descriptive method. Data collection techniques uses interviews, observation, and case study regarding the management of facilities and infrastructure in .The data obtained during the study are described in the form of words to draw conclusions. Based on the data analysis that has been carried out, it can be concluded that: planning for facilities and infrastructure is carried out by looking at the needs then adjusted to the land and funds owned, procurement of facilities and infrastructure is carried out by buying or borrowing and funds obtained from foundations, BOP, and donations from parents of students, use is carried out by analyzing needs, developments and according to the learning theme. maintenance at is carried out routinely, on a scale, and in an emergency. Abstrak. Fasilitas pendidikan sangat menentukan suatu keberhasilan pendidikan, karena sarana prasarana sangat berperan penting dalam proses pembelajaran. Sarana dan prasarana berpengaruh terhadap proses pembelajaran, sehingga menentukan pembelajaran yang berjalan efektif dan efisen. Dengan adanya penelitian ini maka peneliti akan mengkaji tentang pengelolaan sarana dan prasarana meliputi, perencanaan sarana dan prasarana, pengadaan sarana dan prasarana, penggunaan sarana dan prasarana, dan pemeliharaan sarana dan prasarana. Penelitian ini bertujuan memperoleh gambaran pengelolaan sarana dan prasarana di lembaga PAUD. Pendekatan dan metode yang digunakan dalam penelitian ini menggunakan metode kualitatif pendekatan studi kasus. Teknik pengumpulan data menggunakan wawancara, observasi, dan studi kasus mengenai pengelolaan sarana dan prasarana di lembaga PAUD. Data yang diperoleh selama penelitian diuraikan dalam bentuk kata-kata untuk ditarik kesimpulanya. Berdasarkan analisis data yang telah dilakukan dapat disimpulkan yaitu: perencanaan sarana dan prasarana dilakukan dengan melihat kebutuhan kemudian disesuaikan dengan lahan dan dana yang dimiliki, pengadaan sarana dan prasarana dilakukan dengan cara membeli atau meminjam dan dana yang diperoleh dari yayasan, BOP, dan sumbangan orang tua murid, penggunaan dilakukan dengan cara menganalisis kebutuhan, perkembangan dan disesuaikan dengan tema pembelajaran, pemeliharaan di lembaga PAUD dilakukan secara rutin, berskala, dan darurat.